Fatigue performance of bolted shear connectors. Issue 1 (2nd January 2022) - Hosseini, Seyedeh Maryam; Mashiri, Fidelis; Mirza, Olivia
ABSTRACT: A computer-aided engineering (CAE) fatigue life prediction technique is developed in this paper to determine the fatigue strength of bolted shear connectors in composite structures. A relatively new initiative in the composite construction industry is the use of the blind boltshear connector, which provides a sustainable and practical solution to the main limitation of using traditional welded stud regarding reuse of building components. Furthermore, fatigue is one of the major causes involved in fatal mechanical failures of composite structures. However, limited research has been currently undertaken to assess fatigue life of composite structure. Therefore, the fatigue performance of the blind bolt under constant amplitudes cyclic loading has been investigated using ABAQUS/explicit and FE-SAFE programs. First, the dynamic responses of steel-concrete composite structures under sinusoidal load cycles were simulated using ABAQUS/explicit. Then, the stress–strain time history based on the response law of the composite structure was introduced into the FE-SAFE software to obtain a good prediction on the fatigue life of the blind bolt shear connector. As a result, the logarithmic life distributions of the bolted shear connector were calculated using different constant amplitudes.